2011
DOI: 10.1111/j.1742-7843.2011.00824.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide‐Induced Sickness Behaviour Evaluated in Different Models of Anxiety and Innate Fear in Rats

Abstract: Abstract:The fact that there is a complex and bidirectional communication between the immune and nervous systems has been well demonstrated. Lipopolysaccharide (LPS), a component of gram-negative bacteria, is widely used to systematically stimulate the immune system and generate profound physiological and behavioural changes, also known as 'sickness behaviour' (e.g. anhedonia, lethargy, loss of appetite, anxiety, sleepiness). Different ethological tools have been used to analyse the behavioural modifications i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(57 citation statements)
references
References 66 publications
8
43
2
Order By: Relevance
“…Depressive-like behavior in LPS-treated group revealed by marked reduction in the immobility time in FST and TST as compared to vehicle-treated control group. Our behavioral test results are in concordance with the previous experimental studies [3,23,34]. The observed anxiety and depressive-like behavior in behavioral paradigms may be accompanied by the elevation of oxidative stress and neuroinflammation in HC and PFC brain regions as well as by BDNF depletion in the HC region evoked by LPS administration.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Depressive-like behavior in LPS-treated group revealed by marked reduction in the immobility time in FST and TST as compared to vehicle-treated control group. Our behavioral test results are in concordance with the previous experimental studies [3,23,34]. The observed anxiety and depressive-like behavior in behavioral paradigms may be accompanied by the elevation of oxidative stress and neuroinflammation in HC and PFC brain regions as well as by BDNF depletion in the HC region evoked by LPS administration.…”
Section: Discussionsupporting
confidence: 94%
“…Numerous experimental studies suggested the role of oxidative stress and inflammation in anxiety and depressive illness [3,32,33]. LPS is a very well-known endotoxin that can cause anxiety and depressive-like behavior in rodents after central or peripheral administration [3,34,35]. LPS elicits the production of proinflammatory cytokines (IL-β, IL-6, TNF-α) and reactive oxygen species (ROS) that eventually leads to peripheral as well as systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with compound 6g increased the ambulation scores but there was no significant effect observed on rearing scores. The results are in accordance with previous studies [27][28][29]. In addition to change in various behavioral parameters, the compound 6g also increased the levels of serotonin in LPStreated mice brain.…”
Section: Discussionsupporting
confidence: 92%
“…injection of LPS 500 mg/kg BW was used to induce peripheral inflammation (Bassi et al 2012, Iwasa et al 2014. LPS administration induced anorexia, which is in line with previous studies (Gautron et al 2005, Ogimoto et al 2006.…”
Section: Nfkb Activation In the Hypothalamus Is Involved In Lps-inducsupporting
confidence: 84%